The Macroeconomic Effects of Counterpart Funds and the Underlying Foreign Aid - Mulder, Christian (IMF Working Papers; Working Paper, 1992)
Counterpart funds generated through foreign currency or commodity aid have again become an issue of interest, in view of the substantial buildup of these funds. Contrary to the usual approach a model is developed in this paper, which takes account of the budgetary impact, supply-side and money demand effects of counterpart funds and the underlying foreign aid. This model is used to show that counterpart funds need not have any economic impact if their creation, use, and effects are adequately monitored and understood, both by donors and by the authorities in the recipient country. The policy rules that ensure an inflation- and foreign reserves-neutral result from expected and unexpected foreign aid are derived and contrasted with a policy rule regarding unexpected foreign aid that is sometimes observed in IMF programs. A feasible alternative is developed. Various real world complications are shown not to alter the conclusions.